(untitled) (Homoeopathy for All, 2023)
Overweight and obesity is a serious medical condition that affects children and adolescents. Overweight is defined as having excess body weight for a particular height from fat, muscle, bone, water, or a combination of these factors. This article provides an overview of the aetiology, diagnosis, and WHO Classification of over Weight appropriate general & homoeopathic management for controlling the weight.